1990
DOI: 10.1037/0012-1649.26.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Maternal facial behavior and the recognition and production of emotional expression by maltreated and nonmaltreated children.

Abstract: 20 maltreated and 20 nonmaltreated children (ages = 3-7 years) and their mothers were observed during a laboratory play session and 7 home observation visits. Ss facial behavior was video recorded in the lab and coded live by observers in the home. Children also participated in an emotionalexpression recognition task. Data analysis showed that both maltreatment status and mothers' facial behavior were predictors of children's recognition scores. Positive relationships were also found between mothers' and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 32 publications
3
74
0
4
Order By: Relevance
“…This original bias may be strengthened or attenuated by other factors, such as experience or phenotype. When considering a particular type of experience, for example, Camras, Ribordy, Hill, and Martino (1990) and Pollak, Cicchetti, Hornung and Reed (2000) showed that maltreated children tended to perform better than controls in the recognition of anger in masked expressions of emotion, whereas adults with social anxiety disorder performed significantly less well than controls in the recognition of facial expressions of anger (Montagne , Schutters, Westenberg, Van Honk, Kessels & De Haan, 2006). Difference in RTs between women (faster) and men was found to be largest for facial expressions of anger in a study by Hampson, van Anders and Mullin (2006).…”
Section: Discussionmentioning
confidence: 99%
“…This original bias may be strengthened or attenuated by other factors, such as experience or phenotype. When considering a particular type of experience, for example, Camras, Ribordy, Hill, and Martino (1990) and Pollak, Cicchetti, Hornung and Reed (2000) showed that maltreated children tended to perform better than controls in the recognition of anger in masked expressions of emotion, whereas adults with social anxiety disorder performed significantly less well than controls in the recognition of facial expressions of anger (Montagne , Schutters, Westenberg, Van Honk, Kessels & De Haan, 2006). Difference in RTs between women (faster) and men was found to be largest for facial expressions of anger in a study by Hampson, van Anders and Mullin (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Extant work indicates that some deficits exist in the emotion understanding of children at-risk for psychological disorder. For example, abused and maltreated children exhibit deficits in the recognition of face expressions of emotion (e.g., Camras, Grow, & Ribordy, 1983;Camras & Rappaport, 1993;Camras et al, 1990;Camras et al, 1988). Maltreated children, children at risk for disruptive behavior disorders, and ''hardto-manage'' preschoolers demonstrated poorly developed understandings of the causes of emotion, for example, by providing fewer appropriate examples of triggers or cues for emotion (e.g., Camras, Sachs-Alter, & Ribordy, 1996;Cook, Greenberg, & Kusche, 1994;Greenberg et al, 1995;Rogosch, Cicchetti, & Aber, 1995;Shipman & Zeman, 1999).…”
Section: Emotion Understanding: Psychopathological Populationsmentioning
confidence: 99%
“…Although child abuse is a known risk factor for the development of psychopathology (Kendler et al, 2000;MacMillan et al, 2001;Malinosky-Rummel & Hansen, 1993), the precise mechanisms linking the experience of maltreatment earlier in life to the development of psychopathology are largely unknown. Even before the emergence of psychopathological syndromes, maltreated children often evince unusual patterns in their abilities to recognize, express, and regulate emotional states (Camras et al, 1990;Camras, Sachs-Alter, & Ribordy, 1996;Pollak, Cicchetti, Hornung, & Reed, 2000). Relatedly, social information processing studies have revealed that when compared with nonabused aggressive children, physically abused aggressive children may be distinguished by biases in early stages of information processing (Dodge, Bates, & Pettit, 1990;Dodge, Lochman, Harnish, & Bates, 1997;Weiss, Dodge, Bates, & Pettit, 1992).…”
mentioning
confidence: 99%